The Profile of IPSAS-Adopters - Donia Ben Amor; Salma Damak Ayadi (Journal of Accounting and Management Information Systems (JAMIS), 2019)
Research question: What is the general profile of countries adopting IPSAS in accounting, institutional and economic terms? Motivation: IPSAS are perceived as the benchmark of public sector's accounting standardization. Their adoption becomes highly promoted by several institutional organizations such as the World Bank and the IMF. Following previous literature review about IPSAS-adoption, researchers focused on only both factors (Ilie & Miose, 2012) and effects (Christiaens et al., 2015; Opanyi, 2016) of the use of these standards. Hence, this study focus on the specificities of IPSAS-adopters. Idea: This research aims to determine the profile of countries adopting IPSAS internationally for the year 2016. Also, it suggests an empirical treatment of countries' economic risk. Indeed, this axis was not treated by previous IPSAS researches. Thus, we add to the literature review by analyzing, empirically the profile of IPSAS-adopters. Data: Data sources are the World Bank, the FMI and IPSAS Board. Moreover, we propose two new measures for the public-market security and for the accounting-system's modernization and transparency. Tools: A logistic regression is applied to test the theoretical hypotheses. Then, the test of marginal effect was applied in order to detect the most common character among IPSAS-adopters. Findings: The result of the empirical study showed that IPSAS-adopters have a modern accounting system based on accruals. These countries have a flexible legal system and an internationally legitimated private accounting system based on IFRS. However, there is any relationship between "IPSAS-adoption" and "the public-market's security". Moreover, the test of marginal effect indicates that the most widely character among IPSAS-adopters the use of IFRS. Contribution: Determining IPSAS-adopters' profile is a new research's axis. It is useful for countries' stakeholders that look for accounting, institutional and economic profiles of these entities.
Keywords: M41; 650; Accounting; public sector; IPSAS; profile; contingency model